The role of the community pharmacist in breast cancer survivorship services - Tutt, Lydia (2020)
Background: Breast cancer is one of the most common cancers in the UK and incidence is increasing. Efforts to promote early diagnoses along with advances in treatments mean people are surviving for longer with breast cancer. This, coupled with the long-term treatment requirements of the condition, have created increasing demand for primary care-based services to support survivors. The current role of community pharmacists in cancer services focuses largely on prevention and early diagnosis. However, as one of the most accessible healthcare providers in primary care, community pharmacists have potential scope to take on a more significant role in supporting breast cancer survivors. The aim of this study was to identify the opportunities for community pharmacists to develop their role in providing support and improving health outcomes for people living with and after breast cancer.